Recent advances on the role of nanomaterials for improving the performance of photovoltaic thermal systems: Trends, challenges and prospective. (March 2022) - Tyagi, Praveen Kumar; Kumar, Rajan; Said, Zafar
Abstract: Due to the ever-increasing demand for energy globally, photovoltaic (PV) modules have grown as a vital exploration field in recent years. Photovoltaic/thermal (PV/T) systems are expected to be the future of renewable energy due to their enormous potential to meet two critical energy needs: electricity and low-grade thermal energy. Nanotechnology has already shown enormous success in the solar field. This paper provides an extensive review of the use of nanofluids (NF) and nano-enhanced phase change materials (NEPCM) for thermal energy storage (TES) applications in PV/T systems. This paper emphasizes the effect of nanomaterials on the thermo-physical properties such as thermal conductivity ( k ), latent heat, subcooling, phase change duration, phase change temperature, viscosity, and density, as well as thermal cycle stability of the phase change materials (PCMs) at various operating temperatures. The literature review shows that the melting point temperature, k, and TES density of PCMs are the critical selection criteria for the TES applications with an extensive operating temperature range. It is also found that these materials usually improve the PV/T system efficiency, while the k of NEPCM depends on the size, shape, concentration, and type of the nanomaterials. Alongside the critical review of the aspects mentioned above, this paper also underlines the future scope of study in this paradigm. It is estimated that this study will provide more insights into the fundamentals and perceptions of the PV/T systems, leading to the augmentation of the thermal performance of nanomaterial-based PV/T systems integrated with PCM or NEPCM. Graphical Abstract: ga1 Highlights: A detailed review of recent advances on the role of nanomaterials for improving the performance of PV/T systems is presented. Thermal energy storage systems are classified and discussed in detail. Emphasis is given on influence of nanoparticles on the thermo-physical properties of PCMs. Recommendations are made regarding future research directions.